THE EMBODIMENT OF SOCIAL CHARACTER VALUES IN AN INDONESIAN EFL TEXTBOOK : A Content Analysis - Velentina Rizki Sutari, - (2018)
This present study tried to discover social character values in the seventh grade English textbook entitled When English Rings a Bell published by Indonesian Ministry of Education and Culture. It also aimed to explain how those values are promoted in the textbook. Employing a methodology of qualitative content analysis, this study revealed that social character of responsibility, honesty, discipline, courtesy, caring, tolerance, teamwork, and confidence are inculcated in seventh grader's When English Rings a Bell textbook. The values are those established in the 2013 Curriculum. The study also discovered that there are other additional positive social values taught in the textbook, including humility, friendship, respect, and initiative. These values are promoted through the integration to the teaching materials in various written text such as instruction, dialogue, monologue, and task. Among all values discovered, responsibility, discipline, and confidence are the most frequent values that When English Rings a Bell tries to cultivate in students. The result of the study indicated that discipline, responsibility, and confidence are values that have to be promoted as early as possible to children and they are urgently needed for the young as long as Indonesia curriculum goal and the national education's goal are concerned.